Phenotypic and functional characterization of lymphocytes that bind human microvascular endothelial cells in vitro. Evidence for preferential binding of natural killer cells. - Bender, J R (1987)
The microvascular endothelium has been postulated to be a critical target in the rejection of vascularized allografts. This study was undertaken to examine the ability of human sheep erythrocyte rosette forming lymphocytes (E-RFC) to form stable conjugates with microvascular endothelial cells (EC), and to assess whether a receptor-ligand interaction mediates this event. Human foreskin microvascular EC monolayers were used as targets of chromium-51-labeled E-RFC in a quantitative adherence assay. Binding was saturable, displaceable by unlabeled E-RFC, augmented by recombinant interleukin 1 (rIL-1) and inhibited by anti-LFA1 antibody. The Leu-11+ lymphocyte subset, known to be enriched for natural killer (NK) cells, bound preferentially. Only the EC-adherent lymphocyte fraction contained NK effectors, which lysed EC and classical NK targets. Thus, NK cells adhere to microvascular EC via a specific receptor-ligand interaction. The possibility exists that such binding occurs in recipients of vascularized allografts, representing the initial stage of graft rejection.